Methane and carbon dioxide cycles in lakes of the King George Island, maritime Antarctica - Thalasso, Frederic; Sepulveda-Jauregui, Armando; Cabrol, Lea; Lavergne, Celine; Olgun, Nazli; Martinez-Cruz, Karla; Aguilar-Munoz, Polette; Calle, Natalia; Mansilla Muñoz, Andres Omar; Astorga España, Maria Soledad (My University, 2022)
Freshwater ecosystems are important contributors to the global greenhouse gas budget and a comprehensive assessment of their role in the context of global warming is essential. Despite many reports on freshwater ecosystems, relatively little attention has been given so far to those located in the southern hemisphere and our current knowledge is particularly poor regarding the methane cycle in non-perennially glaciated lakes of the maritime Antarctica. We conducted a high-resolution study of the methane and carbon dioxide cycle in a lake of the Fildes Peninsula, King George Island (Lat. 62 degrees S), and a succinct characterization of 10 additional lakes and ponds of the region. The study, done during the ice-free and the ice-seasons, included methane and carbon dioxide exchanges with the atmosphere (both from water and surrounding soils) and the dissolved concentration of these two gases throughout the water column. This characterization was complemented with an ex-situ analysis of the microbial activities involved in the methane cycle, including methanotrophic and methanogenic activities as well as the methane-related marker gene abundance, in water, sediments and surrounding soils. The results showed that, over an annual cycle, the freshwater ecosystems of the region arc dominantly autotrophic and that, despite low but omnipresent atmospheric methane emissions, they act as greenhouse gas sinks.
Keywords: fluxes; dissolved gases; greenhouse gas sink/source; microbial gene abundance